Novel extremely acidic lipases produced from Bacillus species using oil substrates. (1st January 2014) - Saranya, P; Kumari, H Sukanya; Jothieswari, M; Rao, B Prasad; Sekaran, G
Abstract: The extremely acidophilic microorganisms Bacillus pumilus and Bacillus subtilis were isolated from soil collected from the commercial edible oil and fish oil extraction industry. Optimization of conditions for acidic lipase production from B . pumilus and B . subtilis using palm oil and fish oil, respectively, was carried out using response surface methodology. The extremely acidic lipases, thermo-tolerant acidic lipase (TAL) and acidic lipase (AL), were produced by B . pumilus and B . subtilis, respectively. The optimum conditions for B. pumilus obtaining the maximum activity (1, 100 U/mL) of TAL were fermentation time, 96 h; pH, 1; temperature, 50 °C; concentration of palm oil, 50 g/L. After purification, a 7.1-fold purity of lipase with specific activity of 5, 173 U/mg protein was obtained. The molecular weight of the TAL was 55 kDa. The AL from B. subtilis activity was 214 U/mL at a fermentation time of 72 h; pH, 1; temperature, 35 °C; concentration of fish oil, 30 g/L; maltose concentration, 10 g/L. After purification, an 11.4-fold purity of lipase with specific activity of 2, 189 U/mg protein was obtained. The molecular weight of the extremely acidic lipase was 22 kDa. The functional groups of lipases were determined by Fourier transform-infrared (FT-IR) spectroscopy.